Carbon microtube/graphene hybrid structures for thermal management applications1. Issue 36 (28th September 2015) - Bi, Hui; Huang, Haining; Xu, Feng; Lin, Tianquan; Zhang, Hui; Huang, Fuqiang
<x xml:space="preserve">Abstract</x> Carbon microtube/graphene hybrid structures were prepared as supporting frameworks to significantly improve the thermal transport properties of octadecanoic acid.